One hour enzymatic synthesis of structure lipids enriched unsaturated fatty acids from silkworm pupae oil under microwave irradiation. Issue 2 (12th February 2019) - Wang, Jin‐Zheng; Liu, Xi; Li, Wen‐Jing; Song, Wen‐Miao; Herman, Richard Ansah; Sheng, Sheng; Wu, Fu‐An; Wang, Jun
Abstract: BACKGROUND: The silkworm pupae of Bombyx mori L. are considered to be a valuable unsaturated fatty acids (UFAs) resource. Enzymatic transesterification, which can produce structured lipids (SLs), is regarded as a desirable approach to utilize this resource, but requires long reaction time. A method to reduce the reaction time and obtain novel SLs is thus desirable. Hence, microwave irradiation was employed to reduce the reaction time and obtain novel SLs. In addition, high‐performance liquid chromatography with an evaporative light scattering detector was employed to investigate the contribution of the fatty acids (FAs) after microwave irradiation. RESULTS: One hour was required for a 1:5 substrate ratio of silkworm pupae oil (SPO):oleic acid (OA) using a solvent‐free system catalysed by Lipozyme RM IM (7%) at 60 °C with microwave irradiation at 50 W to obtain the novel SLs. The relative content of polyunsaturated FAs glyceride increased from 51.1% to 81.0%, and the relative content of glycerol trioleate (OOO) in SPO obtained in the microwave reactor was twice as high as that in the shaker reactor. In addition, the relative content of OA was increased from 3.9% to 35.8% in total compared with the products from the shaker reactor. Furthermore, the changes of α ‐helix relative content of Lipozyme RM IM were observed after the reaction under the microwave irradiation. CONCLUSION: The results indicated that variations in the FA distribution of enzymatic transesterification reactions caused by microwave irradiation could aid the addition of OA and enrichment of UFAs. © 2019 Society of Chemical Industry